2007
DOI: 10.1002/jat.1302
|View full text |Cite
|
Sign up to set email alerts
|

NF‐kB and caspases are involved in the hyaluronan and chondroitin‐4‐sulphate‐exerted antioxidant effect in fibroblast cultures exposed to oxidative stress

Abstract: Oxidative stress, inflammation and apoptosis play a critical role in the onset and progression of cellular damage. It was previously reported that hyaluronan (HA) and chondroitin-4-sulphate (C4S) were able to protect human skin fibroblasts from oxidative stress. This antioxidant activity is due to the chelation of transition metal ions. Nuclear factor kB (NF-kB), complexed with the inhibitory protein IkB alpha, is an ubiquitous response transcription factor involved in inflammatory reactions and acts by induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
(37 reference statements)
0
26
0
1
Order By: Relevance
“…We previously reported that HA and C4S were able to reduce free radical damage in fibroblast cultures exposed to FeSO 4 plus ascorbate [Campo et al, 2008]. The actions of HA and C4S were also able to inhibit NF-kB and executioner caspase activation [Campo et al, 2008].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We previously reported that HA and C4S were able to reduce free radical damage in fibroblast cultures exposed to FeSO 4 plus ascorbate [Campo et al, 2008]. The actions of HA and C4S were also able to inhibit NF-kB and executioner caspase activation [Campo et al, 2008].…”
Section: Discussionmentioning
confidence: 96%
“…The actions of HA and C4S were also able to inhibit NF-kB and executioner caspase activation [Campo et al, 2008]. We hypothesized that the inhibition of NF-kB DNA binding to the nucleus may be the consequence of HA plus C4S reduced ROS production in the fibroblasts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…42,43) In addition, it was reported to reduce cell damage by scavenging free radicals, inhibiting the activation of apoptosis, and eliciting an anti-inflammatory effect at the synovial membrane and chondrocyte level. 26,44,45) These cytoprotective actions of CS may reduce the toxicity of PAMAM dendrimers.…”
Section: Fig 7 In Vivo Gene Expression Of Each Complex Administeredmentioning
confidence: 99%
“…While direct effect of HA or DS on keratinocyte apoptosis is unknown, our results provide evidence that their presence may have the indirect effect of reducing apoptosis in vitro compared to non treated specimens and are in line with recently reported results of HA effects on fibroblasts. 9 Evaluation of the molecular mechanism involved in this process was not within the scope of our study. We did not directly observe tissue necrosis on the rims, but as indicated in Table 2 and shown in Fig.…”
Section: Apoptosismentioning
confidence: 99%